ANALISIS PENGARUH PERSISTENSI BIDANG DISKONTINU TERHADAP KESTABILAN LERENG BATUAN TERKEKARKAN MENGGUNAKAN METODE ELEMEN HINGGA - Donald R Nainggolan; S Koesnaryo; Barlian Dwinagara (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2020)
This research was conducted in an quarry andesite mining, which has a single slope with a height of 46m-48m. the degree of slope approximately from 860-900. The rock mass condition at the research location is a jointed rock with joint length was recorded along the scanline between 0.5 m-17m and have a joint spacing between 6cm-190cm. At shallow depths, the rock failure are more controlled by discontinuities. The research is concern on the relationship between slope stability and the persistence condition (K) of the discontinuous. Persistence (K) is the ratio between the joint length (JL) to the length of the failure plane, the failure plane is a combination of the length of joint and the rock bridge. Rock bridge (RBR) is defined as an area of intact rock that separates coplanar and non-coplanar discontinuous planes in the rock mass. To determine the effect of discontinuous persistence on slope stability, persistence modeling was carried out using the average of joint length measurement results and analyzed using the finite element method. The final results of the study showed that an increase in the average persistence of 10% affected a decrease in the safety factor (FK) by 6.7%, an increase in the value of landslide probability (PL) by 59%, and an increase in normal stress by 7.3%. There was a significant change in FK and PL when the persistence is greater than 80%.